How to Keep 18 Million People Moving. - Guizzo, E.
This paper discusses Sao Paulo's operation of the most complex bus system. And in an experiment to reduce pollutant emissions, Sao Paulo will test a small number of hydrogen-fuel-cell buses on one of the city's busiest busways. The concept of a modern, high capacity bus system is often called bus rapid transit. BRT differs from conventional bus operations in that the coaches often newer, more comfortable vehicles - run on dedicated portions of roadways, and stations feature off-vehicle fare collection and slightly elevated platforms to speed up boarding.
Keywords: Bus rapid transit; Complex bus system; Hydrogen-fuel-cell.; Pollutant emission reduction